Brokering between (not so) overt and (not so) covert networks in conflict zones. Issue 1 (2nd January 2020) - Stys, Patrycja; Verweijen, Judith; Muzuri, Papy; Muhindo, Samuel; Vogel, Christoph; Koskinen, Johan H.
ABSTRACT: There is a tendency to consider covert networks as separate from overt networks. Drawing on data from the Democratic Republic of the Congo, we demonstrate that this is not the case and identify how covert and overt networks are mutually constitutive. While most studies of African brokers have relied on network metaphors like 'Big Men' and 'social membranes', we consider the embeddedness of 'covert' networks in 'overt' networks explicitly. We perform two analyses on a large original dataset encompassing 396 partially overlapping ego-nets obtained from a hybrid link-tracing design. An ego-net analysis reveals a large degree of homophily and a deep embeddedness of the different networks. A multilevel exponential random graph model fitted to the reconstructed network of a 110-node subset shows that demobilised combatants are the actors likely to broker between armed groups, state forces, and civilian blocs, suggesting their capacity to broker peace or foment war.